2021
DOI: 10.21511/im.17(3).2021.14
|View full text |Cite
|
Sign up to set email alerts
|

The impact of e-marketing orientation, technological orientation and learning capacity on online SME performance

Abstract: Currently, Internet penetration is accelerating across the country in Bangladesh, which, in particular, has led to the simultaneous development and growth of online businesses. Due to increased internet availability and accessibility, a number of small and medium enterprises (SMEs) continue to operate using an Internet-driven online platform. This context requires a research effort to investigate the underlying factors that might influence the business performance of online SMEs. Thus, the aim of the study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Through this extension, some studies (e.g. Al Asheq et al, 2021) were found to show a positive correlation between e-marketing and the marketing performance of small business enterprises, while only a small number of studies (e.g. Brodie et al, 2007) showed a positive correlation between e-marketing and marketing activities.…”
Section: E-marketing Usage and Marketing Activities Of Small Business...mentioning
confidence: 97%
See 2 more Smart Citations
“…Through this extension, some studies (e.g. Al Asheq et al, 2021) were found to show a positive correlation between e-marketing and the marketing performance of small business enterprises, while only a small number of studies (e.g. Brodie et al, 2007) showed a positive correlation between e-marketing and marketing activities.…”
Section: E-marketing Usage and Marketing Activities Of Small Business...mentioning
confidence: 97%
“…Several studies (e.g. (Al Asheq et al, 2021;Eid & Elbeltagi, 2006;Stockdale & Standing, 2004) have found that E-marketing positively influences the marketing performance through new sales, new customers, development of new markets, good customer relationships, increased market share, increased brand equity, and increased productivity.…”
Section: E-marketing Usage-marketing Performance Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Training and development are significant determinants of employees' motivation in the working environment, which helps to develop knowledge, skills, and abilities in their work (Asheq et al, 2021). However, training means learning from the trainer that assists in buildup strength among the workers, and they can easily learn what they unknown.…”
Section: Training and Developmentmentioning
confidence: 99%
“…Facebook is fast and most publicity platform for the advertisement of every organization either offline or online. In the case of economic growth, the banking sector plays an important role in Bangladesh (Rahaman et al, 2021;Karim, 2020;Kumar et al, 2019;Latif et al, 2019;Karim et al, 2018;Asheq et al, 2021;Islam et al, 2014;Akther et al, 2021;Asheq et al, 2021). The house we live in may have been mortgaged to a private bank, the car we drive or the taxi and the bus we ride to our office may have been bought with money borrowed from yet another bank.…”
Section: Introductionmentioning
confidence: 99%